Tracking funding to inform action: mapping the award landscape for research on pandemic and epidemic intelligence - Emilia Antonio; Zaharat Kadri-Alabi; Isabel Redies; Barbara Tornimbene; Oliver Morgan; Alice Norton (Health Research Policy and Systems, 2026)
Abstract Background Despite innovations driven by the COVID-19 response, research to improve surveillance and public health intelligence remains fragmented and poorly translated into practice. In 2024, the WHO Hub for Pandemic and Epidemic Intelligence conducted an exercise to identify research priorities aimed at coordinating robust evidence generation and methodologies for effectively responding to global health emergencies. Our aim was to analyse the extent to which the current research award landscape for epidemic-prone diseases aligns with the pandemic and epidemic intelligence research priorities. Methods We used the Pandemic Preparedness: Analytical Capacity and Funding Tracking (Pandemic PACT) grant tracker, a database which monitors research funding for pandemic-prone diseases to identify research activities aligned with the pandemic and epidemic intelligence priorities. We extracted data from the Pandemic PACT database on 15 September 2025. We analysed the focus of awards, funding entities and funding amounts committed, and research locations. Results From January 2020 to September 2025, only 1.6% of the 26 028 global research awards identified through the Pandemic PACT grant tracker focussed on pandemic and epidemic intelligence. Twenty-nine funders, mostly based in North America and Europe, invested at least US$ 503 million in this research field with few jointly funded research awards. There were limited investments across all research priority areas, and investments into evidence translation to policy and data governance research were particularly lacking. Most funding was for research being conducted in high-income countries. Conclusions Targeted research investments and multi-country research collaborations through improved coordination among funders will be crucial for enhancing effective global surveillance systems and future pandemic preparedness.